Fast cycle time-driver of innovation and quality - Choperena, Alfredo M.
Alfredo M. Choperena tells how Sanofi Diagnostics Pasteur cut the time it took to commercialize a new immunoassay system without compromising quality.
Rapid product development needn't cost more or hurt quality, as this commercial example demonstrates.
Speed, quality and innovation in product development are often viewed as mutually exclusive goals. In the highly competitive environment of the nineties, time to market with new products can make or break companies. Yet, the rapid development of high-quality, highly innovative, sophisticated systems has been an elusive goal for many. Under these premises, to gain a competitive edge, one must use a practical and effective approach to systems development that improves on the old paradigms of quality, speed and innovation. Fast Cycle Time (FCT) techniques translated into a common-sense approach to product development can be the ticket to achieving this very desirable condition. Following a set of practical FCT guidelines can effectively help complete development of innovative systems in record time without compromising quality.
Keywords: Fast cycle time (FCT).